If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(u + -2) + -3u = 2(u + -6) Reorder the terms: 4(-2 + u) + -3u = 2(u + -6) (-2 * 4 + u * 4) + -3u = 2(u + -6) (-8 + 4u) + -3u = 2(u + -6) Combine like terms: 4u + -3u = 1u -8 + 1u = 2(u + -6) Reorder the terms: -8 + 1u = 2(-6 + u) -8 + 1u = (-6 * 2 + u * 2) -8 + 1u = (-12 + 2u) Solving -8 + 1u = -12 + 2u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-2u' to each side of the equation. -8 + 1u + -2u = -12 + 2u + -2u Combine like terms: 1u + -2u = -1u -8 + -1u = -12 + 2u + -2u Combine like terms: 2u + -2u = 0 -8 + -1u = -12 + 0 -8 + -1u = -12 Add '8' to each side of the equation. -8 + 8 + -1u = -12 + 8 Combine like terms: -8 + 8 = 0 0 + -1u = -12 + 8 -1u = -12 + 8 Combine like terms: -12 + 8 = -4 -1u = -4 Divide each side by '-1'. u = 4 Simplifying u = 4
| 3(2+y)-y=6+2(y+1) | | 17x+16=4(4x+6) | | 2(u+1)+4u=3(2u-1) | | 4(y-3)-6y=2(y+6) | | -2(x+6)-6x=4(x+3) | | 3w-26=-8(w+6) | | 9(x+5)=2x-18 | | 8v+32=-8(v-2) | | 32.50+.04(m-30)= | | 32.50+.04(60-30)= | | 32.50+04(60-30)= | | 32.50+.04(40-30)= | | 8(3x+1)=4x-9x | | 26c+891=-71 | | 0.02-0.03(x+3)=0.05(3-x) | | 1.2m+7.5m+2.1=6.3 | | 5-8+2t= | | 3(3n+5)=9(9n+9)+8 | | 18p-35=0 | | 0.04(y-4)+0.20y=0.10y-1 | | -3t-2t-5-4= | | 3(5z-1)-4(z+9)=4(z+1) | | 4x+6=-6+2x+18 | | 4[5-(4-6x)]+3x=3(9x+5)-11 | | 4[5-(4-6x)]+3x=3(9x-5)-11 | | 21x-7=5(4x+2)-3 | | -8+11= | | -15+12= | | x*2=16 | | 10(v+3)-4v=3(2v+1)-7 | | 3y+2x=26 | | 12/.075=x+10 |